If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 2b + -14 Reorder the terms: 18 = -14 + 2b Solving 18 = -14 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 18 + -2b = -14 + 2b + -2b Combine like terms: 2b + -2b = 0 18 + -2b = -14 + 0 18 + -2b = -14 Add '-18' to each side of the equation. 18 + -18 + -2b = -14 + -18 Combine like terms: 18 + -18 = 0 0 + -2b = -14 + -18 -2b = -14 + -18 Combine like terms: -14 + -18 = -32 -2b = -32 Divide each side by '-2'. b = 16 Simplifying b = 16
| -10+(-28)= | | (1.6*10^8)(5.8*10^6)/(4*10^6) | | 8z+36=68 | | 5x^3=3600 | | y=-3(x-2)+5 | | 69+66= | | 7n+15-10n=180 | | 4x+28=70 | | 3(7)-4y=-19 | | -3x-5=100 | | 6n-1+5=-20 | | 3456x+56x=4567.89x-2 | | 2n-3n+5n= | | 47-43=180 | | 9x^2-131x+410=0 | | 18m=15 | | 5(2m+3)=95 | | 215+3x=165 | | 3(-1)-y=3 | | 6x-17+40=180 | | X/4-7/4= | | 165+3x=215 | | 9x^6/12x^2 | | 12(f+10)=156 | | 83/4÷70 | | 5+7r+6-4r= | | 12+4(-6)=12 | | 4b+39=63 | | 5m+4s=62 | | 3x^2+9x+24=0 | | x+8+14x=28 | | 9-7[6-(6y-4)]= |